Fungi in the normal human external ear - Ruslan, Raudha Ezaty; Rajagopalan, Raman; Ng, Kee Peng (Medknow Publications, 2019)
Aim: The aim of this study is to determine the presence of fungi in the human external ear. Materials and Methods: A total of 84 specimens of skin scraping were taken from the external ear canals of 46 randomly selected adult ears with their consent. Patients were 15 males and 31 females, with a mean age of 51 years (22 years to 86 years). Of these, 38 patients were from both the ears, and 4 each from right or left ear, respectively, making it a total of 84. These samples were sent to the microbiology laboratory for potassium hydroxide staining for fungal elements and then cultured in sabouraud dextrose agar with olive oil. If fungus was detected on the agar after 2-4 weeks of incubation, the type of fungus was read and verified by a microbiologist. Results: Forty specimens were positive (47.6%) and 44 were negative for fungal culture. The positive culture was Malassezia furfur in 31 (77.5%) and other fungi (Candida albicans 1, Candida parapsilosis 6 and Aspergillus species 2) in 9 (22.5%). Conclusion: There are fungi as commensals in the external human ear, M. Furfur is the most common fungus. © 2019 Indian Journal of Otology Published by Wolters Kluwer - Medknow.